How Online Reviews are Read - Lockie, Maree (Auckland University of Technology, 2015)
Online reviews, a form of electronic word-of-mouth (eWOM) communication, have fast become a relied on source of information. It is for this reason we need to further understand how it is consumers read this information; what is important to them and what personal or individual characteristics influence how they read. To do this, a mixed method approach was taken using 30 participants. First, an eye-tracking experiment was conducted with participants reading an online review website. Following this, an online questionnaire was conducted to measure the individual characteristics of the reader. Both sets of data were analysed separately, using coding and SPSS frequencies respectively. Both sets of data were then combined and analysed on SPSS using linear stepwise regression and logistic stepwise regression. Results show that specific review factors do work together and gazes and actual liking of online reviews does interplay somewhat. Most significantly, certain personal characteristics and traits do influence the way in which online reviews are read.
Keywords: Online reviews; Personality; Eye tracking